GEOCHEMISTRY AND TECTONO-MAGMATIC AFFINITY OF MAFIC EXTRUSIVE AND DYKE ROCKS FROM THE OPHIOLITE MELANGE OF THE SW ZAGORJE-MID-TRANSDANUBIAN ZONE (MT. MEDVEDNICA, CROATIA) - Slovenec, Damir; Lugović, Boško (Ofioliti, 2009)
Mafic extrusive rocks occasionally intersected by dolerite dykes are the most abundant fragments of oceanic crust in the lower Callovian to upper Valanginian ophiolite mélange exposed on the Mt. Medvednica, at the SW tip of the Zagorje-Mid-Transdanubian Shear Zone. The mélange includes a chaotic mixture of various extrusive rocks which may be analogues of the oceanic rocks derived from (at least) two different tectonic settings. The extrusive and dyke rocks of this mélange are geochemically classified into three magmatic groups: high-Ti group of N-MORB-like with arc signatures (Ti/V = 26.3-38.5), medium- Ti group (Ti/V = 20.2-23.0) and low-Ti group showing untypical LREE depleted [(La/Sm)cn = 0.49-0.62] IAT-like signatures (Ti/V = 13.2-18.0). All three geochemical groups of magmas were successfully monitored by clinopyroxene geochemistry. The magmas have consistent initial Nd-isotopic values (eNd(T=163 Ma) +5.9 to +6.3) and initial 87Sr/86Sr ratios (0.703748-0.704286) suggesting a similar parental source related to the initial stage of intraoceanic subduction of a back-arc basin ridge. It represents the new crust formed from melts derived from LREE extremely depleted MORB-type mantle which was affected by concomitant metasomatism and partial melting in a suprasubduction forearc setting. K-Ar ages on plagioclase separates indicate uppermost Bathonian - lower Oxfordian magmatic activity between 165±3.3 Ma and 160±3.3. A geodynamic model for the Mt. Medvednica ophiolites, part of the Repno oceanic domain of the Meliata-Maliak oceanic system, is here proposed. There are many common geochemical and geological correlation features between the Mt. Medvednica and Szarvaskö ophiolites, located in NE Hungary that allow to integrate them in the same oceanic domain, whereas this is not obvious in the case of the Dinaric ophiolites.